SITUS INVERSUS, BICUSPID AORTIC VALVE, SUBAORTIC MEMBRANE AND AORTIC STENOSIS-A RARE COMBINATION - Chaudhry, Imtiaz Ahmed; Khan, Inamullah; Zamir, Ali Gohar; Pervaiz, Farrah; Akbar, Haijra (Pakistan Armed Forces Medical Journal, 2020)
Situs inversus, dextrocardia with subarctic membrane and bicuspid aortic valve is a rare entity, making surgical procedures complicated and challenging. We describe a case of a 23 year old male patient, presenting with a history of dyspnoea on exertion. Lung fields were clear and the apical impulse was palpable in the fifth inter costal space in the right mid-clavicular line. A chest roentogram showed dextrocardia, an elevated lt hemi-diaphragm with the gastric bubble on the right side Aortic valve stenosis with dextrocardia was suspected from the history and clinical examination and a transthoracic echocardiogram (TTE) was preformed. Surgical setup was the same as for routine cardiac surgical procedures; with the exception that the surgeon was on the opposite side (left side of the patient). The postoperative course was uncomplicated and the patient remains asymptomatic at one year follow up. His recent echos show regression in ventricular hypertrophy and acceptable gradients across the prosthetic aortic valve.